The effective promotion of trace amount of Cu on Ce/WO3‐ZrO2‐TiO2 monolithic catalyst for the low‐temperature NH3‐SCR of NOx. (20th November 2017) - Li, Yuanshan; Xu, Haidi; Feng, Xi; Liu, Shuang; Chen, Yaoqiang
Abstract: The selective catalytic reduction of NO x with NH3 (NH3 ‐SCR) activity of 0.10 g/g CeO2 /WO3 ‐ZrO2 ‐TiO2 (Ce/WZT) in low temperature range was greatly enhanced by the addition of 0.00010 g/g Cu (Cu/Ce mass ratio = 1:1000). The temperature of complete NO x conversion ( T 90 ) decreased as much as 36  °C (from 263  °C to 227  °C) under a gas hourly space velocity (GHSV) of 30 000 h −1 . XPS, NH3 /O2 ‐TPD, H2 ‐TPR, XRD, and FTIR characterizations revealed that the interaction between Cu and Ce, more active oxygen species, stronger NH3 and NO oxidation ability, better redox ability, together with the abundant Brønsted acid sites contributed to better catalytic activity of 0.00010 g/g Cu‐0.10 g/g Ce/WO3 ‐ZrO2 ‐TiO2 (CC/WZT) catalyst at low temperatures. Abstract : Even with 0.00010 g/g, the addition of Cu still could possess an obvious effect on strengthening the low temperature NH3 ‐SCR performance over Ce/WZT.